2002
DOI: 10.3201/eid0812.020532
|View full text |Cite
|
Sign up to set email alerts
|

First Isolation ofWest Nile virusfrom a Patient with Encephalitis in the United States

Abstract: West Nile virus (WNV) was isolated from a patient who developed encephalitis while undergoing treatment with CHOP (cyclophosphamide, hydroxydoxorubicin, vincristine [Oncovin], predisone) and rituximab for a non-Hodgkin B-cell lymphoma. Both standard reverse transcription–polymerase chain reaction (RT-PCR) and Taqman RT-PCR established the diagnosis of WNV infection from cerebrospinal fluid (CSF). Several whole blood samples and one serum sample underwent further testing. CSF and serum samples were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
62
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 14 publications
6
62
1
Order By: Relevance
“…One of the patients who acquired transfusion transmitted West Nile virus infection subsequently died, and donated organs to four transplant recipients, three of whom developed meningoencephalitis (9). Although, these and other case reports have suggested that organ transplant patients may have more severe disease compared to immunocompetent patients, it is only with seroprevalence data that any true estimates regarding rates of asymptomatic and symptomatic disease can be made in this population (9,10,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…One of the patients who acquired transfusion transmitted West Nile virus infection subsequently died, and donated organs to four transplant recipients, three of whom developed meningoencephalitis (9). Although, these and other case reports have suggested that organ transplant patients may have more severe disease compared to immunocompetent patients, it is only with seroprevalence data that any true estimates regarding rates of asymptomatic and symptomatic disease can be made in this population (9,10,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition, quantitative RT-PCR demonstrated 1.1 ϫ 10 6 viral RNA copies/ml of CSF in a fatal case of human WNV encephalitis. 8 Given the dearth of information regarding quantitative aspects of natural WNV infection in mammalian hosts, future work is needed to define more clearly the roles of viral load and replication in encephalitic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Infection of the nervous system is characteristic of the most severe cases of WNV disease, often resulting in death or long-term neurologic sequelae (26). Pathologies associated with extraneural sites of infection have also been reported, including acute renal failure (11,24).…”
mentioning
confidence: 99%